2019
DOI: 10.1016/j.fertnstert.2019.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circular RNA expression profiles in cumulus cells from patients with polycystic ovary syndrome

Abstract: Objective: To determine aberrant circular RNA (circRNA) expression profiles in cumulus cells from polycystic ovarian syndrome (PCOS) patients and identify their potential biological functions. Design: Circular RNAs microarray analysis of human tissue. Setting: University hospital. Patient(s): A total of 40 women, including 20 PCOS patients and 20 non-PCOS patients. Intervention(s): None. Main Outcome Measure(s): A circRNA microarray containing probes that interrogate 21,442 human circRNAs to investigate differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…CircRNAs are differentially expressed in endometrial biopsies of repeated implantation failure patients and controls. Data of granulosa cells from Jia et al (2018), Che et al (2019), and Shen, Li, et al (2019); of sperm from Capel et al (1993); of embryo development from Ragusa et al (2019) and Dang et al (2016); of endometrial biopsies of RIF patients from Liu et al (2017). circRNAs, circular RNAs; RIF, recurrent implantation failure…”
Section: Circrnas In Embryogenesismentioning
confidence: 99%
“…CircRNAs are differentially expressed in endometrial biopsies of repeated implantation failure patients and controls. Data of granulosa cells from Jia et al (2018), Che et al (2019), and Shen, Li, et al (2019); of sperm from Capel et al (1993); of embryo development from Ragusa et al (2019) and Dang et al (2016); of endometrial biopsies of RIF patients from Liu et al (2017). circRNAs, circular RNAs; RIF, recurrent implantation failure…”
Section: Circrnas In Embryogenesismentioning
confidence: 99%
“…Previous GWAS analysis identified 11 loci associated with PCOS and candidate genes at these loci, which were related to clinical manifestations of PCOS, such as infertility, insulin resistance, T2D and others 4,5 These studies facilitated understanding of the etiologic factors accounting for PCOS. Microarray or RNA-sequencing analysis of oocytes and/or granulosa cells or cumulus cells in women with PCOS has provided insights into understanding of PCOS 610 .…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA expression profiles have been studied in detail in PCOS ( Che et al, 2019 ; Wang et al, 2019 ; Zhang C. et al, 2019 ). Lu et al (2020) found that CiRS-126 acts as a sponge for miR-21 to inhibit ovarian granulosa cell viability.…”
Section: Introductionmentioning
confidence: 99%